Chronic adaptations of shoulder muscle synergies in healthy baseball players - Wambold, M.; Taylor, C.; Tucker, C. A.; Paul, R. W.; Thomas, S. J. (Sports Health: A Multidisciplinary Approach, 2023)
Background: Previous research has demonstrated that muscle synergy structure can adapt owing to training and injury; however, muscle synergies have not been evaluated in baseball players.